Group 4 complexes of salicylbenzoxazole ligands as effective catalysts for the ring-opening polymerization of lactides, epoxides and copolymerization of ε-caprolactone with L-lactide. (12th October 2016) - Pappuru, Sreenath; Chakraborty, Debashis; Vijaya Sundar, J.; Roymuhury, Sagnik K.; Ramkumar, Venkatachalam; Subramanian, Vinodh; Chand, Dillip Kumar
Abstract: A series of salicylbenzoxazole pro-ligand 2-(5-X-benzoxazol-2-yl)-6-R1 -4-R2 -phenol, L1H-L4H were subjected to reaction with titanium, zirconium and hafnium alkoxides. The substituents (R1, R2, X) present in the pro-ligand back bone are (H, H, H) forL1H ; (H, H, Cl) forL2H ; (Br, Br, H) forL3H ; and (Cl, Cl, H) forL4H . The mononuclear Ti complexes, 1a-4a of [M(L)2 (O i Pr)2 ] formulation were prepared by combining the pro-ligandsL1H-L4H with Ti(O i Pr)4 in dry toluene. However, with the addition of H2 O (0.5 M equiv.), the controlled hydrolysis of Ti complex4a in a mixed solvent of THF/toluene produced oxo-bridged dinuclear Ti complex5a having [M(μ-O)(L)2 (O i Pr)]2 formulation in good yield (≥75%) usingL4H as the pro-ligand. The composition of the mononuclear Zr and Hf complexes ofL1H-L4H are found to be quite similar to that of the Ti complexes. Additionally, mononuclear Zr complexes1b-4b and Hf complexes1c-4c were prepared. The oxo-bridged dinuclear Zr and Hf complexes5b and5c were isolated from the controlled hydrolysis reactions of mononuclear Zr and Hf complexes4b and4c . All these complexes were well characterized and crystal structure of six of the fifteen complexes were determined. These complexes were used as initiators for the ring-opening polymerization (ROP) of rac -LA, copolymerization of L -LA with ε- CL and homopolymerization of rac -epoxides. In particular, the dinuclear Zr complex (5b ) was found to exhibit extremely high activity in these polymerization studies. Iso-enriched polymers were observed upon using the Zr and Hf complexes of the pro-ligandsL3H orL4H as the initiator. DFT studies have been carried out on the ROP of lactides initiated by the Ti, Zr and Hf complexes1a, 1b and1c . The results indicated that the activation barrier to reach the transition state using Zr complexes is lower and hence facile as compared to the Ti and Hf complexes. Graphical abstract: Group IV complexes of a series of salicylbenzoxazoles (L1H-L4H ) are prepared. Alkoxide bearing mono nuclear complexes are formed with these pro-ligands (L1H-L4H ). However, control hydrolysis ofL4H supported mono nuclear complexes resulted in alkoxide bearing oxo-bridged dinuclear complexes. These complexes are employed for homopolymerization of rac -LA, rac -epoxides and co-polymerization of L -LA with ε -CL. The complexes ofL4H exhibited superior reactivity for the polymerization reactions. Highlights: High yield synthetic route to new Group 4 compounds containing salicylbenzoxazole ligands. Efficient catalysts for the synthesis of PLA. The synthesis of iso enriched PLAs. The kinetics and mechanistic studies with the ROP of lactides is reported. Active catalysts toward the copolymerization of lactide and caprolactone.